High academic and sports performance. A challenge for higher education institutions and athletes - Omana Guerrero, Alfonso; Vanoni, Giuseppe (European Public & Social Innovation Review, 2025)
Introduction: The crisis in US colleges arises from a dissonance between the educational mission and the lower academic performance of student-athletes, often seen as crucial figures in campus culture. Due to the high academic demands of traditional curricula, this issue has led to conflicting views between coaches, faculty, and administrators. Methodology: a qualitative and interpretive approach based on reviewing papers and NCAA documents. Results: Lower academic performance in athletes due to a lack of adaptation of curriculum as an educational experience to develop social and academic skills, integrating academic credits. Discussion: A faculty member should be included to close the gap and design subject content focused on athletes. Conclusions: Design a curriculum approach based on educational experience as a cornerstone for developing academic and social skills in student-athletes.